VD_FINDINFO HC / 2015 / 181 vom 10. Februar 2015 - VD Tribunal cantonal (2015)
ACTION EN LIBÉRATION DE DETTE, DÉLAI POUR INTENTER ACTION, MOTIVATION DE LA DÉCISION | 83 al. 2 LP, 239 al. 1 CPC (CH), 239 al. 2 CPC (CH)